Spatial distributions of local strains in synthesized diamond crystals from the normalized parameters of Kikuchi patterns - Fodchuk, I.M.; Balovsyak, S.V.; Solodkyi, M.S.; Borcha, M.D.; Băilă, D.-I.; Labudzki, R.; Bonilla, M. (Physics and Chemistry of Solid State, 2024)
This paper presents an improved approach to the calculation and analysis of spatial distributions of local strains in synthesized diamond crystals obtained from the normalized parameters of Kikuchi patterns. This approach consists in the study of Kikuchi patterns using normalized Kikuchi band profiles and the normalized characteristics of the energy Fourier spectrum of the diffraction patterns. The spatial strain distribution for 6 samples of polycrystalline artificial diamond was studied. A cluster analysis of the investigated crystal samples was carried out, which made it possible to establish relationships between the conditions of diamond crystal growth and their strain distributions.